The Role of Marketing Strategy and Artificial Intelligence on Operational Performance with Trust as a Mediating Variable: A Study on Postgraduate Students at Balikpapan University - Nita Prasetia; Dewi Rosita; Lisa Listiqomah; Nurhabibah Nurhabibah; Syahril Hasan (JURNAL ECONOMINA, 2026)
This study analyzes the influence of Marketing Strategy and Artificial Intelligence on Operational Performance with Trust as a mediating variable among postgraduate students at Universitas Balikpapan. A quantitative explanatory design was applied. Data were collected from 32 postgraduate students who actively use digital academic services through structured questionnaires. The analysis employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4. The results show that Artificial Intelligence has a positive and significant effect on Trust (p<0.05), and Trust significantly affects Operational Performance (p<0.05). However, Marketing Strategy does not significantly influence Trust or Operational Performance. In addition, Artificial Intelligence has no direct significant effect on Operational Performance. Mediation analysis indicates that Trust significantly mediates the relationship between Artificial Intelligence and Operational Performance, but does not mediate the effect of Marketing Strategy on Operational Performance. These findings highlight Trust as a key determinant in translating Artificial Intelligence adoption into improved Operational Performance in higher education contexts.